Retracted: Maternal traditional Chinese medicine exposure and risk of congenital malformations: a multicenter prospective cohort study - Ting Peng; Lin‐Liang Yin; Yu Xiong; Feng Xie; Chun‐Ya Ji; Zhong Yang; Qi Pan; Ming‐Qing Li; Xue‐Dong Deng; Jing Dong; Jiang‐Nan Wu (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The potential teratogenic risk of traditional Chinese medicine (TCM) is of widespread concern; however, related evidence is largely absent in humans. This study aimed to compare the prevalence of congenital malformations between pregnant women with and without TCM exposure. Material and methods This was a multicenter prospective cohort study of 17 713 women who participated in a survey on periconceptional TCM exposure. Primary outcome was congenital malformations diagnosed from a survey conducted on the day 42 after delivery. Results A total of 16 751 pregnant women with 273 congenital malformations were included in the analysis. Fetuses exposed to TCM had an increased risk of congenital malformations compared to those without exposure (odds ratio [OR] 2.10; 95% confidence interval [CI] 1.09–4.02) after controlling for potential confounders. There were significant associations with congenital malformations in women with early pregnant exposure (OR 2.04, 95% CI 1.00–4.20) and for those who received ≥2 TCM formulas (OR 5.84, 95% CI 1.44–23.65). Pre‐pregnancy TCM exposure was significantly associated with an increased risk of congenital heart defects (OR 12.69; 95% CI 3.01–53.51). Conclusions Periconceptional TCM exposure is associated with an increased risk of congenital malformation. This effect was cumulative and sensitive to periconceptional age. Therefore, TCM deserves more attention and should be used cautiously for pregnant women and those trying to become pregnant.